(untitled) (American Journal of Agricultural Science, Engineering, and Technology, 2022)
In modern life, users use the cloud spaces for storing important data and valuable information. To avoid security problems, every cloud storage provider requires help from several security mechanisms. Every mechanism has its own security scheme. Most of them use the PBKDF (Password-Based Key Derivation Function) and Salt for generating encryption keys. By analyzing, we found that unique and random Salt plays a vital role for generating keys. But to create powerful keys, we must avoid pseudorandom generators for making salt because hackers can easily crack the key by using it. We have to take inputs from beyond expected sources. We proposed an algorithm by which we can generate Salt by using the client’s real-time environmental information known as Location Information of user, User Time Information with Entropy Data at key generation time. In this paper, we focus on simulation result and compare each algorithm with the proposed algorithm ULTE. Simulation result represents the whole statistical distribution as stated in the algorithm. The result shows that ULTE has provided excellent performance than other algorithms.